Health-related behaviors among the Lublin Province population - Sitarz, Robert; Kolasińska-Bzoma, Małgorzata; Kolasińska-Gliwa, Ewa J.; Kurylcio, Andrzej; Mielko, Jerzy; Polkowski, Wojciech P.; Maciejewski, Ryszard (Polish Journal of Public Health, 2012)
Introduction. Awareness of risk factors that induce the formation and development of cancer is an important element in the fight against cancer. Appropriate health-related behavior may limit the formation and development of cancer. Maintaining a healthy weight, physical activity, abstinence from alcohol and healthy diet are the main preventive measures, not only in the prevention of cancer. Aim. The aim of the research was to explore the state of knowedge about health behaviors of the Lublin Province population. Material and methods. The study included 1352 respondents presenting with different reasons to their family doctor. The research tool was a questionnaire, while the research method was a diagnostic survey. The questions concerned different aspects of a healthy lifestyle. Results. Our study showed that the population of the Lublin Province has insufficient and incomplete knowledge about health behaviors. Log-linear analysis showed that the statistically significant factors in maintaining a healthy weight, physical activity, abstinence from alcohol and diet are the interactions of age, education, place of residence and gender. Conclusions. The conclusions of the survey confirmed that there is an urgent need to raise awareness about healthy behaviors. Activities aimed at promoting a healthy lifestyle must include gender, social, economic and cultural habits.